Remoción de arsénico por biomasa no viva de Cyperus laevigatus L. y Typha domingensis Pers. en aguas subterráneas del centro poblado de Medio Mundo, Huaura - Acero Herrera, Maria Doris (2025)
The research sought to determine the influence of non-living biomass of Cyperus laevigatus L. and Typha domingensis Pers on the removal of arsenic in groundwater. The parameters pH, electrical conductivity, dissolved oxygen, total hardness, total dissolved solids and total arsenic content in the groundwater samples were evaluated. The non-living biomass used was obtained from 20 plants from the Albuferas de Medio Mundo wetland, Huaura. These were washed, dried, fractionated and sieved. In addition, arsenic adsorption and removal calculations were carried out, for which water was exposed to different doses of biomass. The results of the initially evaluated parameters were within the norm, except for the total arsenic content with 1.15 mg·L⁻¹. The results of the removals and maximum arsenic adsorption capacities were 91,04 %; 1,047 mg·g⁻¹ and 77,39 %; 0,89 mg·g⁻¹ for C. laevigatus and T. domingensis, respectively. It is concluded that, the non-living biomass of Cyperus laevigatus was more efficient in reducing As-induced contamination in groundwater under optimal pH (6) and dose (15 g·L⁻¹) conditions.